The Descriptive Study on Students’ Anxiety in Speaking Class at English Educational Department of Pgri University of Banyuwangi in the Academic Year 2017/2018 - Nunung Ekawati; Wageyono; Abdul Halim (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2019)
This study is aimed at describing the factors that cause students’ anxiety in speaking class and the strategies used by the students to overcome it. This research is categorized as descriptive qualitative research. It involved all the students of English educational department of PGRI University of Banyuwangi in the academic year 2017/2018 as the subjects of the research. The instruments were the observation sheets, reflection sheets, and a voice recorder. The data were collected through observations and interviews with the students and English speaking lecturer. The researcher also made data categorization before formulating the findings. The findings of the study describe five factors that cause anxiety. The first factor is fear of making mistakes. The mistakes that commonly happened here are on pronunciation, grammar, and vocabulary. The second factor is the speaking tasks which demands classroom presentation. It is also related to students’ lack of confidence, preparation, and practice. The third is students’ self perceptions. The factor is about students’ thought and estimation towards their own capability in mastering the speaking skill which can influence their speaking performance. The next is gap of competence. The factor is dealing with students’ competence in English compared with others. The last is the role of the English speaking lecturer. It is related to lecturer’ ability to maintain suitable classroom activities for the students because it will affect the psychological condition of the students as well. The study also found some strategies used by students to cope with their anxiety. Those strategies are memorization, cognitive, and affective strategies.